Design of a mobile application for the control of pet care - Andrade Arenas, Laberiano Matías (2023)
Activities they perform. A problem that apparently is not very important arises or becomes more evident. Talking about the carelessness that we often, without being intentional, have with our pets, the circumstances force us mostly to have tragic endings with them. Therefore, with the advancement of technology, we have the opportunity to greatly reduce this end and thus give utility to the current resources being presented. The objective of the research work is to develop a prototype of a mobile application using the Balsamiq mockup tool and take as a reference the care model of experts in animal care. In this way, it is possible to have better control and monitoring of the health and other care of our pets. For this use, the Rational Unified Process (RUP) methodology since it is the most appropriate for producing high-quality software, giving us a complete vision in the development of each phase that this methodology presents. Likewise, a positive result is obtained by the expert judgments of the evaluation of the design of our application. As a result, the proposed objective was achieved by obtaining a prototype that can help meet some needs of people who require support in the care of their pets, thus leaving an open the door to continue adding and improving the development of this project.